2015
DOI: 10.1039/c5ra05702g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-aryl-3-C-glycosyl- and unsymmetrical 3,5-diaryl-1,2,4-triazoles from alkylidene-amidrazones

Abstract: A general synthetic method was elaborated for 3,5-disubstituted-1,2,4-triazoles with different groups in positions 3 and 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Among cyclocondensation routes reactions of amidine 1 or acid chloride 2 with amidrazones gave intermediates 4 and 5, respectively, which on heating gave the expected 1,2,4-triazoles 8 [54]; transformations of tosylamidrazone 7 by acid chlorides [53], or reactions of N-acyl thioamides 10 and 12 with hydrazine [59] also led to 8. A further procedure, representing a new synthesis for 1,2,4-triazoles in general, was based on the bromination of imidoylhydrazones 3 to give the surprisingly stable derivatives 6 which were cyclized to 8 under basic conditions [57]. Finally, ring transformations of tetrazole 11 by imidoyl chlorides also gave, via N-benzylated 1,2,4-triazole intermediates, the protected triazoles 8 [55] which were debenzoylated under Zemplén conditions to the test compounds 9.…”
Section: Design and Syntheses Of C-glucopyranosyl Azoles As Glycogen mentioning
confidence: 99%
See 1 more Smart Citation
“…Among cyclocondensation routes reactions of amidine 1 or acid chloride 2 with amidrazones gave intermediates 4 and 5, respectively, which on heating gave the expected 1,2,4-triazoles 8 [54]; transformations of tosylamidrazone 7 by acid chlorides [53], or reactions of N-acyl thioamides 10 and 12 with hydrazine [59] also led to 8. A further procedure, representing a new synthesis for 1,2,4-triazoles in general, was based on the bromination of imidoylhydrazones 3 to give the surprisingly stable derivatives 6 which were cyclized to 8 under basic conditions [57]. Finally, ring transformations of tetrazole 11 by imidoyl chlorides also gave, via N-benzylated 1,2,4-triazole intermediates, the protected triazoles 8 [55] which were debenzoylated under Zemplén conditions to the test compounds 9.…”
Section: Design and Syntheses Of C-glucopyranosyl Azoles As Glycogen mentioning
confidence: 99%
“…Generally applicable reactions were elaborated for the conversion of readily available glycosyl cyanides 67 to various C-glycosyl imine type compounds (Scheme 6). Under reductive conditions in the presence of Raney-Ni, NaH 2 PO 2 , and an added acylhydrazine type reagent tosylhydrazones 65 [91][92][93][94], acylhydrazones 66 [95], imidoylhydrazones 68 [57], semicarbazones and carbamoylhydrazones 69 [95] could be prepared in good to excellent yields. With hydroxylamine and its derivatives this reaction was not feasible, however, transimination of semicarbazones 69 resulted in oximes 70 and 71.…”
Section: Syntheses Of Other Glycomimetics and Their Precursorsmentioning
confidence: 99%
“…[20][21][22] However, when trying to apply this oxidant for cyclization of N'-arylidene-C-glycosyl formamidrazones, a complex mixture of products was obtained which contained less than 20% of monocyclic 1,2,4-triazole. 23 We have shown that the reaction of N'-arylidene amidrazone 2a, easily prepared from amidrazone 1, with PIDA in CH 2 Cl 2 , CHCl 3 , acetonitrile or their mixtures at room temperature for 24-36 h results in the formation of triazole 3a in 12-37% yield (Scheme 1). It has been found that chloroform is the best solvent for the reaction at reflux temperature, in which the reaction is complete in 3 h. Upon cooling the reaction mixture, up to about half of the resulting product (39-47% depending on the loading) precipitates and is easily separated by filtration.…”
mentioning
confidence: 97%
“…triazoles (Scheme 1)[23,24,[41][42][43]. Synthetic studies were started by transformations of tetrazole 1[44] since this method proved to be the most versatile one in previous investigations (Route A)[23].…”
mentioning
confidence: 99%